SISTEM PENGISI DAN PENGATUR TEKANAN UDARA BAN MOBIL SECARA OTOMATIS DENGAN MIKROKONTROLER - Hartono, Hartono; Thomas, Thomas; Isa, Sani M. (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Sometimes to fill a tire with a air pump were made us tired. Not even to fill it up but we must check it up the tire pressure. The process of air pressure filling and control device for car tire automatically using microcontroller is the way of solution to every people to check up the tire easily. The systems can be measure maximum pressure until 50 psi then the system can be check for every change of voltage level to prove there is any leakage of tire. This system can help us more better to know our tire condition easily.